Physiologically Difficult Airway in the Patient with Severe Hypotension and Metabolic Acidosis. (4th September 2020) - Capone, Joseph; Gluncic, Vicko; Lukic, Anita; Candido, Kenneth D.
Abstract : The expertise to recognize and manage the difficult airway is essential in anesthesiology. Conventionally, this refers to anatomical concerns causing difficulties with facemask ventilation and/or with tracheal intubation. Severe derangements in patients' physiology can make induction and intubation likewise difficult, and approximately 30% of critically ill patients had cardiovascular collapse subsequently to intubation. We present the case of a 58-year-old male with a past medical history of type II diabetes and hypertension who presented with altered mental status due to severe metabolic acidosis with a pH of 6.8 on admission to the intensive care unit. The anesthesia team was called to urgently intubate the patient. Upon arrival, the patient was localizing to pain and was hypocapnic, tachycardic, and hypotensive despite ongoing therapy with norepinephrine, vasopressin, and bicarbonate drips. Bedside point-of-care ultrasound showed hyperdynamic left ventricle with no other abnormalities. The patient was induced with IV ketamine, and dissociation occurred with maintenance of spontaneous respirations, which was followed by laryngoscopy and intubation causing only minimal hemodynamic changes. The patient was subsequently dialyzed and treated supportively. He was discharged from the hospital two weeks later—neurologically intact and at his baseline. Combination of hypotension and severe metabolic acidosis is particularly a challenging setting for airway management and a major risk factor for adverse events, including cardiopulmonary arrest. Hemodynamically stable induction agents should be preferred. In addition, sustaining spontaneous ventilation and avoiding periods of apnea in the peri-intubation period is paramount—any buildup of CO2 could push a critically low pH even lower and cause cardiovascular collapse. Sympathomimetic properties of ketamine make this induction agent a particularly appealing choice in this setting. This case report further supports the concept that severe physiologic perturbations—in which conventional induction techniques are not feasible—should be included in the current definition of a difficult airway.